2016
DOI: 10.13170/ajas.1.1.4077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ammonia toxicity on growth performance, cortisol, glucose and hematological response of Nile Tilapia (Oreochromis niloticus)

Abstract: Ammonia is a production limiting factor in the aquaculture media affecting fish production. A study was designed to scrutinize effects of ammonia on growth performance, survival, cortisol and hematological parameters of Tilapia fish. The study examined effects of 96 h-incubation of male and female Tilapia with 3 mg ammonium chloride per a liter of water compared to control. The study has been carried out in the physiology laboratory of the department of animal and fish production, Alexandria University. Fourte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
2
18
0
1
Order By: Relevance
“…Higher mortalities detected in T5 could be attributed to the higher exposure dose of TAN. Fish exposed to lower doses (T1, T2 and T3), showed steady growth up to the end of the of exposure period without significant differences between them, similar results were obtained by Zeitoun et al (2016) who reported reduced values of weight gain, ADG and SGR of Nile tilapia in the presence of ammonia (3 mg ammonium chloride per liter). Increased ammonia reduced growth rate in tilapia Sakala and Musuka (2014); in common carp Kawamoto (1961) and in channel catfish Robinette (1976).…”
Section: Discussionsupporting
confidence: 81%
“…Higher mortalities detected in T5 could be attributed to the higher exposure dose of TAN. Fish exposed to lower doses (T1, T2 and T3), showed steady growth up to the end of the of exposure period without significant differences between them, similar results were obtained by Zeitoun et al (2016) who reported reduced values of weight gain, ADG and SGR of Nile tilapia in the presence of ammonia (3 mg ammonium chloride per liter). Increased ammonia reduced growth rate in tilapia Sakala and Musuka (2014); in common carp Kawamoto (1961) and in channel catfish Robinette (1976).…”
Section: Discussionsupporting
confidence: 81%
“…Hematological parameters revealed increases (P<0.05) in both fish exposed to stressors. There were significant decreases (P<0.05) in red blood cell, hematocrit value and hemoglobin concentration in both males and females of Nile Tilapia after exposure to ammonia toxicity (Zeitoun, et al, 2016). Data given in the present study showed significant decrease in the red blood cell counts (RBCs), hemoglobin (Hb) and hematocrit (Ht) in the Nile tilapia exposed to the ammonia toxicity, the effects were dose-dependent.…”
Section: Discussionsupporting
confidence: 53%
“…Ammonia exists in two forms: ionized ammonia (NH4 + ) and unionized ammonia(NH 3 ), while both are commonly expressed as total ammonia. Remarkedly, even at low concentrations, ammonia possesses a toxic impact on fish, and hence, may cause serious problems in aquaculture production (Morrison and Piper, 1988). The probable effects of high concentration of ammonia on the fish species, reared in collapsible and concrete tanks, include damages to tissue, gill and kidney, as well as a reduction in growth (Rodrigues et al, 2013).…”
mentioning
confidence: 99%
“…The pH value was not different between the R, G, and B groups, which could be because of a greater total amount of bacterial activity that is influenced by the use of artificial light compared to the Natural group. Using a C/N ratio of 20, the TAN concentration has a similar behavior value to pH and it was maintained at levels that are suitable for Nile tilapia, according to [39]. The NH 3 − N values did not exceed the levels that were considered lethal for Nile tilapia during the experiment, and this value remained below the recommended limit of 0.1 mg/L [40].…”
Section: Discussionmentioning
confidence: 98%